Unveiling tobacco struggle in rural areas: field insights and experiences from Rajasthan, India - Viswanathan, Harimadhav; Raghav, Pankaja; Srinivasan, Srikanth; Remany, Aswathy Suseelan; Rajendran, Vinoth; Baskaran, Pritish; Singh, Tanya (Frontiers in Public Health, 2025)
Tobacco use is a significant public health concern in rural India. This case study was conducted in a village of the Jodhpur district in Rajasthan, India. The high prevalence and patterns of tobacco use among the villagers was identified by a situational analysis in the OPD and through household visits, shopkeeper surveys, focus group discussion with health workers, and by engaging with community members, local leaders, and health workers. A general lack of adherence to Cigarettes and Other Tobacco Products Act (COTPA) rules in public places, schools, and points of sale, as well as a gap in awareness regarding the harmful effects of tobacco were found. Seven out of 10 patients attending the OPD and more than half of the village population used tobacco. Smokeless tobacco products like mava, masheri, gutka, and khaini were widely used by everyone, while older men preferred smoking forms. Children as young as 10 years old used tobacco, often encouraged by parents who believed it would suppress hunger. These findings led to the initial focus being given to comprehensive awareness through health education sessions, followed by a multistakeholder approach that engaged local leaders, police, shopkeepers, teachers, and other relevant stakeholders. Activities were conducted at health facility, administrative, and community levels. These strategies focused on awareness activities, more stringent implementation of COTPA, cessation of public display of tobacco products in shops, and the monthly celebration of ‘No Tobacco Day’. The interventions at school led to a significant improvement in the Tobacco-Free Educational Institution (ToFEI) score, from 9 pre-intervention to 90 post-intervention. The outcomes underscore that using these strategies with appropriate adaptations can be effective in tobacco control across diverse settings.